1972
DOI: 10.1073/pnas.69.9.2734
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Surfaces and the Diversity of Possible Roles of Circadian Organization in Photoperiodic Induction

Abstract: It is an established fact that circadian rhythmicity is often somehow involved in the physiology of photoperiodic induction. It is shown, however, that there are three possible ways in which such rhythmicity could be involved. For the most part available data are inadequate to discriminate among these three roles, only one of which is covered by "Binning's Hypothesis." Emphasis is given to a previously ignored possibility in which circadian organization is involved in photoperiodism-but not as the clock res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
153
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(159 citation statements)
references
References 6 publications
6
153
0
Order By: Relevance
“…Light at the beginning of the day entrains the photoperiodic clock, and when the light period is long enough to extend into the photoinducible phase, photoperiodic induction occurs [1,4,11]. The results from several species of birds are consistent with this model of photoperiodic induction called the external coincidence model [6,[12][13][14][15].…”
Section: Introductionsupporting
confidence: 71%
“…Light at the beginning of the day entrains the photoperiodic clock, and when the light period is long enough to extend into the photoinducible phase, photoperiodic induction occurs [1,4,11]. The results from several species of birds are consistent with this model of photoperiodic induction called the external coincidence model [6,[12][13][14][15].…”
Section: Introductionsupporting
confidence: 71%
“…The hourglass clock is a computerized version of the Megoura clock and is able to generate photoperiodic responses similar to those obtained experimentally with Lees's protocols performed with the mite (Vaz Nunes and Veerman, 1986b). However, in the mite, the positions of the peaks and troughs observed in Nanda-Hamner experiments were not related to the total cycle length (T) as suggested by Pittendrigh (1972); instead, they were re- Pittendrigh et al (1984). a.…”
Section: The Hourglass Timer-oscillator Counter Modelmentioning
confidence: 80%
“…This concept later was called "internal coincidence" (Pittendrigh, 1972) to differentiate it from external coincidence; it suggests that light has a single role (entrainment) and not the dual roles (entrainment and photoinduction) inherent in the latter. Table 1 lists several theoretical versions of internal coincidence: phase relationships between two light-entrainable master oscillators or pacemakers, either coupled in a complex pacemaker (Model 7) or independent of each other (Model 8); phase relationships between a pacemaker and a slave (Model 9); and phase relationships among several slaves driven by the same (or different) pacemaker(s) (Model 10).…”
Section: Internal Coincidence and The Multioscillator Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Morris, 1973;Bhatti and Morris, 1978a,b;Brady, 1982;Reebs, 1994), and it has been shown that in birds, the transparency of the skull is sufficient to allow intensities of around 10 lux to reach a photoreceptor in the cerebrum (Hader and Tevini, 1987). It is now generally accepted that photosensitivity (the threshold of an animal's sensitivity to light) is governed by circadian rhythm, but that photoperiodic reactions (the animal's behavioural response to light intensity, such as going to roost) are stimulated only when light coincides with photosensitive periods (Pittendrigh and Morris, 1964;Pittendrigh, 1972;Hader and Tevini, 1987). This theory, known as the 'coincidence model', explains why birds will only be stimulated to go to roost in the evening, even though the environmental conditions (such as light levels) acting as the cues to roosting may occur at other times of the day (Saunders, 1977;Applin and Cloudsley-Thompson, 1982;Brady, 1982).…”
Section: Introductionmentioning
confidence: 99%